Promoting health literacy in school: A systematic literature review and meta-analysis - Amalia Pradipta, Vianka; Pramana Situmorang , Risya (Universitas Negeri Jakarta, 2024)
Health literacy is the capacity of an individual to locate, read, comprehend, and internalize health-related information in their environment. This study aims to: (1) identify the design of health literacy learning in Biology subjects at the high school level, (2) map out learning designs that can affect students' health literacy in Biology subjects at the high school level, (3) analyzing the design learning can affect students' health literacy in Biology subjects at the high school level. The chosen research methodology involves a systematic literature review of articles released between 2011 and 2021. This comprehensive analysis encompasses 20 articles and adheres to the established PRISMA guidelines. The data analysis technique uses thematic analysis, which includes methods to identify, analyze, and report themes in the data. The results of the distribution visualization show that the research topics are grouped into four clusters: PBL, media, school policies, and curriculum. The results of the research topic test were based on the highest Cohens'd criteria, namely PBL topics, curriculum, school policies, and media. The PBL variable with the media, school policy with the media, and school policy with the curriculum have the most vital relationships in the correlation test between concerns. We can use educational techniques like PBL and practical, theoretical tasks to improve health literacy. Due to its student-centered design, which encouraged collaborative problem-solving by utilizing knowledge and information from many sources, the learning model received higher results.